POLLINATION OF SOLAR PANELS AND KEEPING THEM CLEAN - Axmedova, Xurshidakhon Ne’matjon qizi (Educational Research in Universal Sciences, 2023)
Dusting of the transparent working surface of the solar panel in the article, as a result, electricity consumption levels decrease and pollen purification is studied.